Small-molecule drugs development for Alzheimer's disease - Yao, Weiwei; Yang, Huihui; Yang, Jinfei (Frontiers in Aging Neuroscience, 2022)
Alzheimer's disease (AD) is an irreversible, progressive neurodegenerative brain disorder with no effective therapeutic drugs currently. The complicated pathophysiology of AD is not well understood, although beta-amyloid (Aβ) cascade and hyperphosphorylated tau protein were regarded as two main causes of AD. Other mechanisms, such as oxidative stress, deficiency of central cholinergic neurotransmitters, mitochondrial dysfunction, and inflammation, were also proposed and studied as targets in AD. This review aims to summarize the small molecule drugs developed based on the pathogenesis and gives a deeper understanding of AD. We hope it can give help for scientists to find new and better treatments to gradually conquer the problems of AD in future.